PERTUMBUHAN TERONG DENGAN PEMBERIAN PUPUK ORGANIK CAIR AMPAS TEBU YANG DIDEKOMPOSISI TRICHODERMA HARZIANUM (R3) - Istiqamah Istiqamah; Mukarlina Mukarlina; Siti Khotimah; Rahmawati Rahmawati (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2026)
Eggplant (Solanum melongena L.) variety Yuvita is one of the eggplant cultivars grown in West Kalimantan, Indonesia. The cultivation of eggplant in peatland areas of West Kalimantan faces several constraints, particularly the low availability of macro and micronutrients in the soil. Improvement of eggplant production can be achieved through the application of liquid organic fertilizer (LOF). This study aimed to evaluate the effect of liquid organic fertilizer derived from sugarcane bagasse decomposed using Trichoderma harzianum (R3) on the growth of eggplant. The experiment was arranged in a Completely Randomized Design (CRD) with four treatments, namely control (P0), 25 mL/L (P1), 50 mL/L (P2), and 75 mL/L (P3). The results showed that the application of sugarcane bagasse-based LOF significantly affected fresh weight, dry weight, and total chlorophyll content of eggplant plants. However, it did not significantly influence plant height and number of leaves. The best concentration was 50 mL/L, which produced a fresh weight of 8.80 g, a dry weight of 0.594 g, and a total chlorophyll content of 131.38 mg/L.